The electronic structure of the antimony chalcogenide series: Prospects for optoelectronic applications - WATSON, GRAEME; ALLEN, JEREMY (My University, 2014)
In this study, density functional theory is used to evaluate the electronic structure of the antimony chalcogenide series. Analysis of the electronic density of states and charge density shows that asymmetric density, or `lone pairs?, form on the SbIII cations in the distorted oxide, sulphide and selenide materials. The asymmetric density progressively weakens down the series, due to the increase in energy of valence p states from O to Te, and is absent for Sb2Te3. The fundamental and optical band gaps were calculated and Sb2O3, Sb2S3 and Sb2Se3 have indirect band gaps, while Sb2Te3 was calculated to have a direct band gap at ?. The band gaps are also seen to reduce from Sb2O3 to Sb2Te3. The optical band gap for Sb2O3 makes it a candidate as a transparent conducting oxide, while Sb2S3 and Sb2Se3 have suitable band gaps for thin film solar cell absorbers.
PUBLISHED
Keywords: Antimony chalcogenides; DFT